2022
DOI: 10.1101/2022.01.28.22270022
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Continuing inequalities in COVID-19 mortality in England and Wales, and the changing importance of regional, over local, deprivation

Abstract: Background: Observational studies have highlighted that where individuals live is far more important for risk of dying with COVID-19, than for dying of other causes. Deprivation is commonly proposed as explaining such differences. During the period of localised restrictions in late 2020, areas with higher restrictions tended to be more deprived. We explore how this impacted the relationship between deprivation and mortality and see whether local or regional deprivation matters more for inequalities in COVID-1… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Accordant results across the included SEP measures are consistent with SEP encompassing a range of resources relevant to health, representing a fundamental cause of health inequalities, irreducible to a single factor [ 48 ]. Many previous studies have only considered area-level SEP [ 6 , 9 , 49 ]. This is often the only available data when using population-based COVID-19 data but limits our understanding of how within-area differences in SEP affect COVID-19 outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordant results across the included SEP measures are consistent with SEP encompassing a range of resources relevant to health, representing a fundamental cause of health inequalities, irreducible to a single factor [ 48 ]. Many previous studies have only considered area-level SEP [ 6 , 9 , 49 ]. This is often the only available data when using population-based COVID-19 data but limits our understanding of how within-area differences in SEP affect COVID-19 outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In England using the Office for National Statistics (ONS) index of multiple deprivation (IMD) data and COVID-19 testing data from Public Health England (PHE), it was found that the association between more disadvantaged area-level SEP and worse COVID-19 outcomes reversed towards the end of 2020, with higher levels of neighbourhood deprivation appearing protective against COVID-19 infection and mortality [ 6 , 9 ]. This was a period when locally targeted lockdown restrictions were implemented, with lower area-level deprivation becoming risk-inducing for infection and severity for several months before reverting [ 6 , 9 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite a trend towards worsening inequalities, we found an attenuation of the effect of SEP on SARS-CoV-2 infection at time-period 3 when local lockdown restrictions were introduced, supporting previous conclusions from population level data for SEP and SARS-CoV-2 infection. 10,14,35…”
Section: Discussionmentioning
confidence: 99%
“…Individual and contextual risk factor associations for COVID-19 have changed over time. 7-10 Like many high-income countries, in the UK, higher SEP was protective for infection and severity during the early stages of the pandemic. 11-13 However, as shown from Public Health England (PHE) and Office for National Statistics (ONS) data, this association reversed towards the end of 2020 when locally targeted lockdown restrictions were implemented, with high area-level SEP becoming risk-inducing for infection and severity for several months before reverting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation